Engineering three-dimensional bone macro-tissues by guided fusion of cell spheroids - Prabhakaran, Vinothini; Melchels, Ferry P.W.; Murray, Lyndsay M.; Paxton, Jennifer Z. (Frontiers in Endocrinology, 2023)
Introduction: Bio-assembly techniques for the application of scaffold-free tissue engineering approaches have evolved in recent years towards producing larger tissue equivalents that structurally and functionally mimic native tissues. This study aims to upscale a 3-dimensional bone in-vitro model through bio-assembly of differentiated rat osteoblast (dROb) spheroids with the potential to develop and mature into a bone macro-tissue. Methods: dROb spheroids in control and mineralization media at different seeding densities (1×10 4 , 5×10 4 , and 1×10 5 cells) were assessed for cell proliferation and viability by trypan blue staining, for necrotic core by hematoxylin and eosin staining, and for extracellular calcium by Alizarin red and Von Kossa staining. Then, a novel approach was developed to bio-assemble dROb spheroids in pillar array supports using a customised bio-assembly system. Pillar array supports were custom-designed and printed using Formlabs-Clear-resin ® by Formlabs Form2 printer. These supports were used as temporary frameworks for spheroid bio-assembly until fusion occurred. Supports were then removed to allow scaffold-free growth and maturation of fused spheroids. Morphological and molecular analyses were performed to understand their structural and functional aspects. Results: Spheroids of all seeding densities proliferated till day 14 and mineralisation began with cessation of proliferation. Necrotic core size increased over time with increased spheroid size. After bio-assembly of spheroids, morphological assessment revealed fusion of spheroids over time into single macro-tissue of more than 2.5 mm size with mineral formation. Molecular assessment at different time points revealed osteogenic maturation based on the presence of osteocalcin, downregulation of Runx2 (p<0.001) and upregulated alkaline phosphatase (p<0.01). Discussion: With the novel bio-assembly approach used here, 3D bone macro-tissues were successfully fabricated which mimicked physiological osteogenesis both morphologically and molecularly. This bio-fabrication approach has potential applications in bone tissue engineering, contributing to research related to osteoporosis and other recurrent bone ailments.